Implementing SAP CRM : the guide for business and technology managers - Kale, Vivek (Auerbach, 2014)
In today's competitive business environment, most companies realize that the better they can manage their customer relationships, the more successful they will become. Customer Relationship Management (CRM) software systems are key tools for companies to manage the customer-facing processes of their businesses. However, many companies have resisted implementing this most critical customer-oriented application due in large part to the lack of a single-point resource on implementing a CRM system. This book attempts to fill that gap. Implementing SAP® CRM will help technologists and managers come.